2019
DOI: 10.3390/ma12010174
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Flexural Properties of Z-Pinned Carbon Fiber-Reinforced Aluminum Matrix Composites

Abstract: Z-pinning can significantly improve the interlaminar shear properties of carbon fiber-reinforced aluminum matrix composites (Cf/Al). However, the effect of the metal z-pin on the in-plane properties of Cf/Al is unclear. This study examines the effect of the z-pin on the flexural strength and failure mechanism of Cf/Al composites with different volume contents and diameters of the z-pins. The introduction of a z-pin leads to the formation of a brittle phase at the z-pin/matrix interface and microstructural dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Recently, carbon-based reinforcements have been used to impart improvements in the properties of Al-MMCs [ 19 ]. Carbon materials such as carbon fibers [ 20 , 21 ], graphite [ 22 , 23 ], carbon nanotubes (CNTs) [ 24 , 25 ], graphene (G) [ 26 , 27 ] and graphene oxide (GO) [ 28 , 29 ] have been used as reinforcements in Al-MMCs. In graphene-reinforced aluminum matrix nanocomposites, an improvement of 79, 49 and 44% in yield strength, ultimate strength, and Vickers hardness have been reported with 1 wt.% GO addition, and the increase in GO content has led to grain refinement of the composite [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, carbon-based reinforcements have been used to impart improvements in the properties of Al-MMCs [ 19 ]. Carbon materials such as carbon fibers [ 20 , 21 ], graphite [ 22 , 23 ], carbon nanotubes (CNTs) [ 24 , 25 ], graphene (G) [ 26 , 27 ] and graphene oxide (GO) [ 28 , 29 ] have been used as reinforcements in Al-MMCs. In graphene-reinforced aluminum matrix nanocomposites, an improvement of 79, 49 and 44% in yield strength, ultimate strength, and Vickers hardness have been reported with 1 wt.% GO addition, and the increase in GO content has led to grain refinement of the composite [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…[17,20,21] Holographic metasurfaces (HMSs) offer unique advantages in optical imaging applications, including multi-color and three-dimensional displays, [22] virtual reality, [23] augmented reality, [24] and multi-information encoding and display. [25,26] These advantages stem from their ability to manipulate the properties of light, such as phase, [27] amplitude, [28] and polarization. [29] The precise wavefront control is enabled by arranging the meta-atoms in subwavelength scale arrays to generate intricate interference patterns, which form the target holographic images over a wide range of wavelengths, from visible to ultraviolet.…”
Section: Introductionmentioning
confidence: 99%
“…However, enhancing the strength of metal matrix composites by introducing graphene is often at the expense of their plasticity, and its inverse relationship of strength and toughening limits the further development and application of graphene/metal matrix composites, which is essential. The fundamental reason is that during the deformation of the material, the stress concentration at the interface is prone to crack formation, and the crack expansion cannot be effectively hindered in the subsequent deformation [ 20 ]. Numerous studies [ 21 , 22 ] have shown that optimizing the toughness of composites by adjusting the configuration and distribution of graphene is an effective way.…”
Section: Introductionmentioning
confidence: 99%